False consciousness in financial markets: Or is it in ivory towers? - Adi Schnytzer; Sara Westreich (Bar-Ilan University, Department of Economics, 2009)
In general, models in finance assume that investors are risk averse. An example of such a recent model is the pioneering work of Aumann and Serrano, which presents an economic index of riskiness of gambles which is independent of wealth and holds (as might be understood from the adjective 'economic') for exclusively risk averse investors. In their paper, they discuss gambles with positive expected returns which will be accepted or rejected by agents which different levels of risk aversion. The question never asked by the authors (and in most of the finance literature) is: Who is offering these attractive gambles? To arrive at an answer, we extend the Aumann-Serrano risk index in such a way that it accommodates gambles with either positive or negative expectations and is thus suitable for both the risk averse and risk lovers. Once we allow for the existence of risk lovers, it may be shown that in financial markets, many gambles with negative expectations are taken either knowingly or unknowingly so that there are always people that act as if they are risk lovers. The paper concludes with a brief discussion of the implications of our result, in particular that gambling is by no means restricted to the casino or the track.
Keywords: 330; Risiko; Index; Erwartungsnutzen; Risikopräferenz; Finanzsektor; Entscheidung bei Risiko; Theorie